The Story of Writing: From Classical Rhetoric to Rhetoric and Composition - I. B. Korotkina (Высшее образование в России)
Written to commemorate the 10th anniversary of the rubric “Academic Writing and Research Competences” established by the journal’s late editor-in-chief Mikhail Sapunov, the paper focuses on the origins of academic writing and traces its development in terms of rhetoric. The five stages of classical rhetoric are interpreted as five key components of academic writing: research, logic, culture, knowledge, and language. This approach helps visualize academic writing as a wholesome model composed of cognitive and linguistic elements, describe the impact of this model on the rhetorical and publishing conventions of the global academic discourse, and define the problems in knowledge construction as deviations from the model’s unity in various sociocultural contexts. The study concludes that the low quality of an academic text may result from either losing the predominance of the first two stages of rhetoric (invention and arrangement) or of the other three (style, memory, and delivery). The former signifies an ideological pressure on researchers to substitute their own rhetoric with quotes from canonized sources, whereas the latter provokes them to disregard language and style as inferior to research, because of which texts diminish in clarity. In either case, communication lacks in efficiency. The study of academic writing in the historical perspective contributes to better understanding of the latest trends in its development and elicits the problems which impede the quality of Russian scholarly and academic texts.